Electrophysiological effects of the sodium-glucose co-transporter-2 (SGLT2) inhibitor Dapagliflozin on human cardiac potassium channels - Müller, Mara Elena; Petersenn, Finn; Hackbarth, Juline; Pfeiffer, Julia; Gampp, Heike; Frey, Norbert; Lugenbiel, Patrick; Thomas, Dierk; Rahm, Ann-Kathrin (International journal of molecular sciences, 2024)
The sodium-glucose co-transporter-2 (SGLT2) inhibitor dapagliflozin is increasingly used in the treatment of diabetes and heart failure. Dapagliflozin has been associated with reduced incidence of atrial fibrillation (AF) in clinical trials. We hypothesized that the favorable antiarrhythmic outcome of dapagliflozin use may be caused in part by previously unrecognized effects on atrial repolarizing potassium (K+) channels. This study was designed to assess direct pharmacological effects of dapagliflozin on cloned ion channels Kv11.1, Kv1.5, Kv4.3, Kir2.1, K2P2.1, K2P3.1, and K2P17.1, contributing to IKur, Ito, IKr, IK1, and IK2P K+ currents. Human channels coded by KCNH2, KCNA5, KCND3, KCNJ2, KCNK2, KCNK3, and KCNK17 were heterologously expressed in Xenopus laevis oocytes, and currents were recorded using the voltage clamp technique. Dapagliflozin (100 µM) reduced Kv11.1 and Kv1.5 currents, whereas Kir2.1, K2P2.1, and K2P17.1 currents were enhanced. The drug did not significantly affect peak current amplitudes of Kv4.3 or K2P3.1 K+ channels. Biophysical characterization did not reveal significant effects of dapagliflozin on current-voltage relationships of study channels. In conclusion, dapagliflozin exhibits direct functional interactions with human atrial K+ channels underlying IKur, IKr, IK1, and IK2P currents. Substantial activation of K2P2.1 and K2P17.1 currents could contribute to the beneficial antiarrhythmic outcome associated with the drug. Indirect or chronic effects remain to be investigated in vivo.